Risk Factors for Exposure to Laboratory-Confirmed Covid-19 Patients as Early Detection of Workers Groups - Sherly Usman; Titiek Hidayati; Akrom Akrom; Aida Ainun Nisa (Jurnal Aisyah : Jurnal Ilmu Kesehatan, 2022)
The COVID-19 pandemic spreads very quickly this will undoubtedly impact healthcare workers (HCW) for COVID-19 transmission. A safety-oriented co-sufferer service system for all becomes urgent to be realized. The risk factors for COVID exposure to HCW have not been identified to date. The study aims to identify risk factors for COVID-19 exposure in HCW. This study performed a systematic review of selected journals following the study's objectives. Search journals by keywords by the Problem (HCW co-19 infection), intervention (PPE, shift duration, job), Comparison (physical distance, workload, placebo), and Outcome (odds ratio, risk ratio) (PICO) conducted at Pubmed and Google Scholar. The selection criteria include all types of literature published by peer-reviewed journals, original articles, or short communication published in 2019-2020. Researchers extract journal identity, authors, methods, Results, and conclusions. The data extraction is analyzed and presented descriptively. This study reviewed six articles. Undergraduate education, clinician job, and age increase the risk of COVID-19 exposure. Workload factors and types of services related to an increased risk of COVID-19 exposure are working on the night shift, working longer than 8 hours, intubation services, and working in the emergency department (ER). The incomplete personal protective equipment (PPE) and poor quality hand washing and hygiene increase the risk of COVID-19 exposure. HCW felt working under pressure also increased the risk of exposure. A work period of more than ten years and attending training can reduce the risk of COVID exposure. The conclusion is there are several factors related to the risk of COVID exposure, including demographic factors, work schedule factors, work stressors, contact history, types of specialized services, PPE, and hygiene behaviors. Abstrak: Penyebaran pandemi COVID-19 yang sangat cepat akan berdampak pada tenaga kesehatan health care workers (HCW) untuk penularan COVID-19. A safety-oriented co-sufferer service system yang berorientasi pada keselamatan menjadi urgen diwujudkan. Faktor risiko pajanan COVID pada petugas kesehatan belum teridentifikasi hingga saat ini. Penelitian ini bertujuan untuk mengidentifikasi faktor risiko pajanan COVID-19 di petugas kesehatan. Penelitian ini melakukan tinjauan sistematis terhadap jurnal-jurnal terpilih sesuai dengan tujuan penelitian. pencarian jurnal dengan kata kunci berdasarkan Masalah (HCW infeksi co-19), intervensi (personal protective equipment (PPE), durasi shift, pekerjaan), Perbandingan (jarak fisik, beban kerja, plasebo), dan Hasil (rasio peluang, rasio risiko) (PICO) dilakukan di Pubmed dan Google Cendekia.Kriteria seleksi mencakup semua jenis literatur yang diterbitkan oleh jurnal peer-review, artikel asli, atau komunikasi singkat yang diterbitkan pada tahun 2019-2020. Peneliti mengekstrak identitas jurnal, penulis, metode, Hasil, dan kesimpulan. ekstraksi data dianalisis dan disajikan secara deskriptif. Penelitian ini mengulas enam artikel. Pendidikan sarjana, pekerjaan dokter, dan usia meningkatkan risiko paparan COVID-19. Faktor beban kerja dan jenis pelayanan yang berhubungan dengan peningkatan risiko terpapar COVID-19 adalah bekerja pada shift malam, bekerja lebih dari 8 jam, pelayanan intubasi, dan bekerja di Instalasi Gawat Darurat (IGD). alat pelindung diri (APD) yang tidak lengkap dan kualitas cuci tangan dan kebersihan. Petugas kesehatan bekerja di bawah tekanan juga meningkatkan risiko pajanan. Masa kerja lebih dari sepuluh tahun dan mengikuti pelatihan dapat mengurangi risiko terpapar COVID.